Controlled Synthesis of Hollow α-Fe2O3 Microspheres Assembled With Ionic Liquid for Enhanced Visible-Light Photocatalytic Activity - Yin, Hang; Zhao, YuLing; Hua, Qingsong; Zhang, Jianmin; Zhang, Yuansai; Xu, Xijin; Long, Yunze; Tang, Jie; Wang, Fengyun (Frontiers in Chemistry, 2019)
Porous α-Fe2O3 hollow microspheres have been successfully synthesized via an ionic liquid-assisted solvothermal reaction and sequential calcinations. The composition and morphology of the samples were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), nitrogen adsorption. The results indicate that the as-prepared samples are α-Fe2O3 microspheres exhibited a spherical morphology with porous hollow structures. The amount of ionic liquid (1-butyl-3-methylimidazolium tetrafluoroborate [C4Mim]BF4) was found to play a crucial role in the control of these α-Fe2O3 hollow structures. According to the experimental results, the proposed formation mechanisms is also investigated at different durations. Munity quantity ionic liquid was used to synthesize α-Fe2O3 hollow spheres with a large specific surface and excellent photocatalytic performance. More unsaturated coordination sites were exposed to the solution because of the large specific surface area, which helped elevate the efficiency of the electron-hole separation. Thus, under UV light irradiation, the photocatalytic degradation activities of the as-synthesized α-Fe2O3 hollow spheres for Rhodamine B (RhB) dye are 2-3 times higher than that of the normal α-Fe2O3 particles.